Kredibilitas Komunikator Membangun Hubungan Sehat Politik di Siompu Kabupaten Buton Selatan: Kredibilitas Komunikator Membangun Hubungan Sehat Politik di Siompu Kabupaten Buton Selatan - Wa Nur Fida; Muh. Rizal Ardiansyah; Viki Yana (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2024)
Showing quality and intelligence among fellow political competitors is a form of building healthy relationships to show each other's abilities in society. Because intelligence, ability and experience make a person able to compete healthily to attract the attention and sympathy of society. Communication credibility is an important point for every leader to show his skills and seriousness to the community. However, as the era of power and wealth progressed, they became powerful in buying people's votes. People living and still thinking primitively are able to be influenced in such a way by promises which in reality are not commensurate with the reality when they are elected as leaders of the people. Communication credibility exists to be able to implement the public's perception that theory and rhetoric are not only a view to show their seriousness about becoming regional leaders or advancing and prospering the people but can compete in a healthy manner by together having the same dreams and goals to provide progress and peace. and the common welfare of society. Many people are running for mayor and members of the DPR or DPRD of South Buton, so there is a need for healthy relationships and healthy competition so that they continue to neutralize trust and social peace in the community. Healthy political relations are the main point for maintaining ties of brotherhood so that there is no oppression of political power and strength in Siompu, South Buton Regency. The people's choice or vote is very important to determine and make them elected to develop or build this country. However, again, the credibility of effective communication and healthy relationships between political competitors is based on them remaining calm and playing healthily until the public determines their own choices and their confidence in their choices without having to bring down, belittle or destroy each other in the eyes of the public during socializations or public speeches. in front of society.